Smart grid as a solution for renewable and efficient energy - Ahmad, Ayaz; Hassan, Naveed Ul 1979- (Advances in environment engineering and green technologies (AEEGT) book series, 2016)
This book features emergent research and trends in energy consumption and management, as well as communication techniques utilized to monitor power transmission and usage